Basics and Structure of Project Writing in Mathematics (Journal of Nepal Mathematical Society, 2020)
In this article various components of undergraduate project writing in mathematics are listed and discussed. We focus on the basics of a mathematical project writing in which we describe the necessity and usefulness of project writing. We then describe the structure of the project stating its various com- ponents. Finally we give some sample project topics. This article is intended for the students of bachelor level and faculties of mathematics among various universities in Nepal.